2015
DOI: 10.1242/dev.117630
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of the Drosophila Torso-like protein at the blastoderm plasma membrane suggests that it translocates from the eggshell

Abstract: The eggshell serves as a depository for proteins that play an important role in early embryonic development. In particular, the Drosophila eggshell is responsible for transferring asymmetries from the egg chamber to specify the regions at both ends of the embryo through the uneven activation of the Torso (Tor) receptor in its membrane. This process relies on the restricted expression of the gene torso-like (tsl) in subpopulations of follicle cells during oogenesis and its protein accumulation at both poles of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 39 publications
0
33
0
Order By: Relevance
“…Tsl is translocated from the eggshell to the egg plasma membrane, where it enables the regional activation of the Torso tyrosine kinase receptor (Tor) [44]. Ectopic expression of Tsl activates the Tor receptor, leading to developmental abnormality.…”
Section: Development-related Membrane Attack Complex/perforin Proteinsmentioning
confidence: 99%
“…Tsl is translocated from the eggshell to the egg plasma membrane, where it enables the regional activation of the Torso tyrosine kinase receptor (Tor) [44]. Ectopic expression of Tsl activates the Tor receptor, leading to developmental abnormality.…”
Section: Development-related Membrane Attack Complex/perforin Proteinsmentioning
confidence: 99%
“…Torso-like is expressed in specialized follicle cells adjacent to the termini of the mature oocyte (Savant-Bhonsale and Montell, 1993). Torso-like protein is placed in the vitelline membrane (Mineo et al, 2015), and may be involved in processing (Casali and Casanova, First published online 24 January 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Tsl has been detected in the plasma membrane at the two ends of the early embryo (Martin et al, 1994;Mineo et al, 2015) and Tsl bears a MACPF motif (Ponting, 1999), which is found in proteins known to become inserted into lipid bilayers (Lukoyanova et al, 2016). One possibility is that Tsl may modulate the local membrane environment in which Torso resides, perhaps by organizing lipid microdomains and thereby driving the formation of complexes competent to signal.…”
Section: Discussionmentioning
confidence: 99%
“…Tsl becomes localized to the anterior and posterior regions of the vitelline membrane (VM) (Stevens et al, 2003): the inner layer of the eggshell that surrounds the developing embryo. In addition, Tsl has been detected in the membrane of the embryo at the anterior and posterior poles (Martin et al, 1994;Mineo et al, 2015). When tsl is ectopically expressed throughout the follicle cell layer, the resulting embryos exhibit phenotypes similar to those produced by the constitutively active torso gain-of-function alleles (Klingler et al, 1988;Savant-Bhonsale and Montell, 1993;Martin et al, 1994), suggesting that in wild-type embryos, Tsl determines where Torso is activated.…”
Section: Introductionmentioning
confidence: 99%